An Improved Crop Management Increases Grain Yield and Nitrogen and Water Use Efficiency in Rice. Issue 1 (1st January 2013) - Xue, Yaguang; Duan, Hua; Liu, Lijun; Wang, Zhiqin; Yang, Jianchang; Zhang, Jianhua
Abstract : A major challenge in rice ( Oryza sativa L.) production is to achieve the dual goal of increasing food production and resource use efficiency. This study aimed to investigate if an improved crop management (ICM) could increase grain yield, N use efficiency (NUE), and water use efficiency (WUE). Three rice cultivars were field grown at either Yangzhou or Lianyungang, China. in 2009 and 2010. Three treatments, local farmers' practice (LFP), ICM, and N omission, were conducted. The ICM adopted two new techniques, that is, site‐specific N management and irrigation using alternate wetting and moderate drying. Compared with the LFP, the ICM significantly increased percentage of productive tillers, crop growth rate, and contents of cytokinins in plants at mid and late growth stages, nonstructural carbohydrate accumulation in the stem at the heading time, and root oxidation activity, leaf area duration, photosynthetic rate of the flag leaf, and activities of key enzymes involved in sucrose‐to‐starch conversion in grains during grain filling. On average, the ICM increased grain yield by 14.4%, agronomic NUE (kg grain yield increase per kg N applied) by 64.1%, and WUE for irrigation (grain yield over amount of irrigation water) by 36.4% when compared with the LFP. We conclude that the ICM could increase not only grain yield but also NUE and WUE. Improved physiological performances at latter growth stages contribute to increases in grain yield and resource use efficiency.